Interferensi Bahasa Daerah terhadap Penggunaan Bahasa Indonesia dalam Komunikasi Formal - Muhammad Ali Imran; Nurasia Natsir (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This sociolinguistic study examines patterns of regional language interference in formal Indonesian usage across bilingual areas of Indonesia. Through a mixed-methods approach, this research analyzes oral and written data from 240 participants across three strategic bilingual regions: Javanese-Indonesian, Sundanese-Indonesian, and Batak-Indonesian. Data were collected through structured interviews, ethnographic observations, and corpus analysis of formal documents. Quantitative analysis employed linguistic corpus software to identify frequency patterns and interference distribution, while qualitative analysis applied ethnography of communication approaches to understand social contexts and functions of interference in communicative interactions. Findings reveal systematic interference typologies that vary according to linguistic domains. Phonological interference demonstrates the highest resistance to formal register constraints (78% consistency), with Batak-Indonesian speakers showing the highest interference rates (85%), followed by Javanese-Indonesian (74%), and Sundanese-Indonesian (71%). Lexical interference occurs in 65% of samples with significant variation based on communication domains, where Sundanese-Indonesian shows the highest rates (72%). Morphological interference is found in 52% of cases, particularly in affixation and reduplication systems. Syntactic interference shows the highest sensitivity to situational formality, decreasing from 45% in semi-formal communication to 28% in strict formal contexts. Research implications indicate the need for reorienting language policy from corrective approaches toward recognizing interference productivity. Language policies should develop flexible standards that accommodate regional variations and promote positive attitudes toward multilingualism. In educational contexts, integration of contrastive approaches in Indonesian language learning is required, along with development of instructional materials sensitive to students' linguistic backgrounds, and teacher training on managing productive versus corrective interference.This research contributes to Indonesian sociolinguistics through providing comprehensive empirical databases, developing innovative theoretical frameworks, and replicable methodologies for language contact analysis. Findings confirm that regional language interference in formal Indonesian constitutes a productive phenomenon reflecting Indonesia's multilingual vitality. Approaches that recognize productive aspects of interference while optimizing formal communication effectiveness become key to developing language strategies responsive to contemporary multilingual Indonesian realities.